Stories from the field: A most significant change synthesis - Harrington, Larry W.; Douthwaite, Boru; León, C. de; Woolley, Jonathan N. (CGIAR Challenge Program on Water and Food, 2008)
In January of 2007, a number of people working with the CGIAR challenge Program on Water and Food (CPWF) were invited to tell stories about the ‘most significant change’ (innovations or partnerships) they had observed as a result of CPWF activity. This paper aims to pull together some of the threads emerging from these stories, weaving them into a fabric that gives insight into CPWF approaches and achievements. The most significant change (MSC) technique was developed to more effectively moni¬tor and evaluate complex participatory rural development programs in which there is diversity in both implementation and outcomes. It has been referred to as ‘monitoring-without-indicators’ (MSC does not make use of pre-defined quantitative indicators) or ‘the story approach’ (answers to important questions about change are felt to be most readily found in stories of who did what, when and why). Authors of cPwF msc stories included theme leaders, Basin coordinators, Project lead¬ers and Principal Investigators. Most stories were based on experiences in the first call of Competitive Grant Projects. Others emerged from Basin Focal Projects or Small Grant Projects. Authors of stories were self-selected, with a total of 54 stories submitted. These stories were compiled and sent for analysis and screening to key leaders. Two categories of stories were requested: one on “the most significant technical devel¬opment/advance”, the other on “the most significant partnership change”. Within the former, there are stories on technical innovations, institutional and policy innovations, and information and knowledge management. within the latter, stories were submitted on field-level partnerships, basin-level partnerships, and capacity building. Some MSC stories focus on only one of the above categories. However, many discuss the interrelationships among categories, e.g., how an institutional innovation enabled widespread use of a new technology. more than half of the stories are also linked to a specific production environment, e.g., dryland, irrigated or rice-based, salt-affected, or aquatic. These are predominantly stories about technical innovations, and the institu¬tional innovations and partnerships contributing to their success. The remaining stories tend to focus on conceptual frameworks, information and knowledge management, and institutional and policy innovations not closely tied to any particular technology.